2009
DOI: 10.1161/circresaha.108.191007
|View full text |Cite
|
Sign up to set email alerts
|

Kv4 Potassium Channels Form a Tripartite Complex With the Anchoring Protein SAP97 and CaMKII in Cardiac Myocytes

Abstract: Abstract-Membrane-associated guanylate kinase (MAGUK) proteins are major determinants of the organization of ion channels in the plasma membrane in various cell types. Here, we investigated the interaction between the MAGUK protein SAP97 and cardiac Kv4.2/3 channels, which account for a large part of the outward potassium current, I to , in heart. We found that the Kv4.2 and Kv4.3 channels C termini interacted with SAP97 via a SAL amino acid sequence. SAP97 and Kv4.3 channels were colocalized in the sarcolemma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
79
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 48 publications
(49 reference statements)
4
79
0
Order By: Relevance
“…9,10 SAP97 regulates the targeting and localization of cardiac potassium channels, such as Kir2.x 11 and K v 1.5 in myocytes. 10 El-Haou et al 12 recently demonstrated that SAP97 interacts with K v 4.2 and K v 4.3 channels via their PDZ-domain binding motif. They showed that suppression of SAP97 expression in rat myocytes decreases the K v 4.x-mediated current, whereas its overexpression increases it.…”
mentioning
confidence: 99%
“…9,10 SAP97 regulates the targeting and localization of cardiac potassium channels, such as Kir2.x 11 and K v 1.5 in myocytes. 10 El-Haou et al 12 recently demonstrated that SAP97 interacts with K v 4.2 and K v 4.3 channels via their PDZ-domain binding motif. They showed that suppression of SAP97 expression in rat myocytes decreases the K v 4.x-mediated current, whereas its overexpression increases it.…”
mentioning
confidence: 99%
“…Uemura has suggested a molecular role of CaMKII in the ischemic heart, which appeared to be characteristic features reversible and immediate translocation of substantial amounts of CaMKII, and reduced autophosphorylation (Uemura et al, 2002). In addition, the dynamic changes in CaMKII and phospho-CaMKII can also regulate other ion channels of cardiomyocytes, such as potassium and sodium channels (Mori et al, 2000;El-Haou et al, 2009), which have been shown to be involved in Ca 2 + homeostasis in cells.…”
Section: Discussionmentioning
confidence: 99%
“…Originally described in the brain at neuronal synapses (75), there is increasing evidence that these scaffolds play a similar role in the heart (1,7,27,39,45,46,53,61,63,81). It has been shown that interaction of cardiac ion channels with SAP97 occurs with a number of potassium channels including Kv1.5, Kv4, Kir2.2 and 2.3, and the hyperpolarization-activated, cyclic nucleotidegated channels (1,7,27,45,46,61,81).…”
Section: Discussionmentioning
confidence: 99%
“…Originally described in the brain at neuronal synapses (75), there is increasing evidence that these scaffolds play a similar role in the heart (1,7,27,39,45,46,53,61,63,81). It has been shown that interaction of cardiac ion channels with SAP97 occurs with a number of potassium channels including Kv1.5, Kv4, Kir2.2 and 2.3, and the hyperpolarization-activated, cyclic nucleotidegated channels (1,7,27,45,46,61,81). These ion channels interact with SAP97 through standard PDZ-domain binding to the terminal most amino acids of the ion channel (1,27,45,46,53,61,81) and appear to play an important role in regulation of channel density at the cardiac myocyte membranes (1,79).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation